PENDAMPINGAN UMKM PANDAI BESI MELALUI DIGITAL MARKETING DI ERA COVID-19 DESA TEGALHARJO KECAMATAN GLENMORE - Endhang Suhilmiati; Mufidah Yusroh; Nurul Fatimah; Nurul Hidayah (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
Through service activities by way of mentoring as a response to the findings of new habits of UMKM actors in the digital era as well as the era of the covid-19 pandemic, it is necessary to strive for the creation of superior and competitive new business habits, one of which is related to product marketing management throughdigital marketing methods. Starting from packaging to distribution. Marketing means can be through social media such as Instagram, Shopee, Lazada and the other. This strategy is able to contribute to the selling value of blacksmith craftsmen so that product distribution in the domestic market can be saved during the pandemic and provides opportunities for the use of digital marketing for UMKM in Tegalharjo Village, Glenmore Subdistric.